RACISM IN “THE HELP” MOVIE BY TATE TAYLOR (A SOCIOLOGICAL APPROACH) - Mutia R Adam (Universitas Muhammadiyah Gorontalo, 2018)
This research discusses the discrimination by white people to black people in “The Help” Movie. Black people and white people are separated by many rules that make black people is intimidating, so racism is still growing up until generations. This research aims to analyze the history, concept or types of racism and the struggle that also does by black people in “The Help” Movie. This research used descriptive qualitative methods. The researcher used the Sociological approach to identify and to find out the types of racism contained in The Help movie. In addition, from the result of the analysis, it was found that there are 4 types or concepts of racism in “The Help” Movie, such as the internalized, interpersonal, institutional and societal types by using Paradies and William’s theory. In the last result of analysis, the researcher also found the Struggle that does by the black people in “The Help” Movie. Keywords: Movie, Racism, Sociological Approach.